Elevated Serum IL-17 Expression at Cessation Associated with Graves’ Disease Relapse - Jianhui Li; Xiaohua Sun; Danzhen Yao; Jinying Xia (International Journal of Endocrinology)
Background. Antithyroid drug (ATD) treatment occupies the cornerstone therapeutic modality of Graves’ disease (GD) with a high relapse rate after discontinuation. This study aimed to assess potential risk factors for GD relapse especially serum interleukin-17 (IL-17) expression. Methods. Consecutive newly diagnosed GD patients who were scheduled to undergo ATD therapy from May 2011 to May 2014 were prospectively enrolled. Risk factors for GD relapse were analyzed by univariate and multivariate Cox proportional hazard analyses. The association between serum IL-17 expression at cessation and GD relapse was analyzed with relapse-free survival (RFS) by the Kaplan–Meier survival analysis and log-rank test. Results. Of the 117 patients, 72 (61.5%) maintained a remission for 12 months after ATD withdrawal and 45 (38.5%) demonstrated GD relapse. The final multivariate Cox analysis indicated elevated IL-17 expression at cessation to be an independent risk factor for GD relapse within 12 months after ATD withdrawal (HR: 3.04, 95% CI: 1.14–7.67, p=0.021). Patients with higher expressions of IL-17 (≥median value) at cessation demonstrated a significantly higher RFS than those with lower levels by the Kaplan–Meier analysis and log-rank test (p=0.028). Conclusions. This present study indicated elevated serum IL-17 expression at cessation to be a predictor for GD relapse within 12 months.